DETERMINANTS OF INCOME IN THE CULINARY FIELD IN DENPASAR CITY - I Gusti Ayu Putri Okayuni; Ni Nyoman Yuliarmi (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the effect of business capital, length of business, business location, working hours, and education level on the income of culinary business actors in Denpasar City. The background of this study is based on the important role of MSMEs in national economic development, especially in the culinary sector which is one of the mainstays of the Gross Regional Domestic Product (GRDP) of Bali Province. Denpasar City, as the center of economic and government activities, has great potential in developing culinary businesses, but still faces challenges in increasing the income of its business actors. This study uses a quantitative approach with an associative design. The research sample was determined proportionally through proportionate stratified random sampling and respondents were taken using accidental sampling techniques in four sub-districts in Denpasar City. Primary data were collected through observation, structured interviews, and questionnaires, while secondary data were obtained from related government agencies. Data analysis was carried out using multiple linear regression, supplemented with classical assumption tests, as well as F and t tests to test the significance of the influence of independent variables simultaneously and partially. The results of the study showed that simultaneously, business capital, length of business, business location, working hours, and education had a significant effect on culinary business income. Partially, the variables of business capital, length of business, working hours, and education have a positive and significant influence on income. However, the variable of business location shows a negative and insignificant influence.